Charitable trusts and cryptoassets: opportunity, or the asset of discord? - Lloyd Brown (Trusts & Trustees, 2023)
In written evidence submitted to Parliament in 2022, the Charity Commission for England and Wales outlined three types of “cryptoasset-related risk exposure” that can directly affect charitable trusts. These include: (i) fundraising donations; (ii) moving funds internationally; and (iii) investment. This article’s purpose is to demonstrate that, out of these forms of risk exposure, “investment” is currently the greatest issue for charities. Charity trustees possess a broad investment power and may be tempted to invest in crypto to financially benefit their funds. However, extreme caution should be heeded before investing in cryptoassets, given their complexity and volatility.